Pengaruh E-Samsat, Kualitas Pelayanan, dan Pemutihan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Tabanan - Dea Tri Nurcahyani; I Ketut Yudana Adi; Gde Herry Sugiarto Asana (AKUNTANSI 45, 2026)
This study was motivated by the declining compliance of motor vehicle taxpayers in Tabanan Regency despite the continuous increase in the number of vehicles. This condition is reflected in the high level of tax arrears and taxpayer compliance rates that have remained below fifty percent in recent years. This study aims to analyze the influence of e-Samsat, service quality, and tax amnesty programs on motor vehicle taxpayer compliance in Tabanan Regency. The sample used in this study consisted of 100 respondents who were motor vehicle taxpayers, selected using the simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS 25 software. The results showed that e-Samsat had no effect on motor vehicle taxpayer compliance. Meanwhile, service quality and tax amnesty programs significantly influenced motor vehicle taxpayer compliance. These findings indicate that service quality and tax amnesty policies play an important role in improving taxpayer compliance, while e-Samsat has not yet shown a significant effect in this study. The implications of this study are expected to serve as evaluation material for local governments in improving taxpayer compliance through the optimization of public services, the effectiveness of tax amnesty programs, and the development of a more accessible and user-friendly e-Samsat system to support timely motor vehicle tax payments in Tabanan Regency in a sustainable manner.